2012
DOI: 10.1080/0965254x.2012.734845
|View full text |Cite
|
Sign up to set email alerts
|

An organizational learning perspective on conceptualizing dynamic and substantive capabilities

Abstract: While researchers have conceptualized both dynamic and substantive capabilities in a variety of ways, there are still no established measures for either dynamic or substantive capabilities. Although learning has been referred to as a specific type of process underlying the evolution and development of dynamic capabilities, the deep connection between dynamic capabilities and organizational process research has not yet been adequately explored. There is a need for conceptualization and operationalization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
5
25
0
1
Order By: Relevance
“…Other studies in India and Pakistan have not used probability sampling methods for similar reasons (e.g. Ali et al, 2012;Jeswani et al, 2008;Ryan & Tipu, 2013) Similar to these studies, we found data collection in Pakistan to be a challenging affair.…”
Section: Data Collection Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…Other studies in India and Pakistan have not used probability sampling methods for similar reasons (e.g. Ali et al, 2012;Jeswani et al, 2008;Ryan & Tipu, 2013) Similar to these studies, we found data collection in Pakistan to be a challenging affair.…”
Section: Data Collection Methodssupporting
confidence: 81%
“…In total, we received 275 usable responses (8.1% response rate), which is in line with similar studies in emerging economies (e.g. Ali et al, 2012;Jeswani et al, 2008;Ryan & Tipu, 2013):…”
Section: Data Collection Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…Hoskisson, Eden, Lau, and Wright (2000) made it clear that there are some issues faced by researchers in the strategy field of emerging countries such as, challenge in investigating subjects randomly, and representatively; difficulty in gaining access to top managers; lack of trust between researchers and respondents. Indeed, many literatures from developing countries, such as Pakistan and India, reported similar results (Ali, Peters, & Lettice, 2012;Aslam, Blome, Roscoe, & Azhar, 2018;Ryan & Tipu, 2013). For example, Aslam et al (2018) who collected data in Pakistan reported that the response rate was only 8.2%.…”
Section: Sample and Datamentioning
confidence: 80%
“…According to research findings, half of authors (21) have neglected this important step. Getting advices from experts minimizes deviations and misconceptions of measurement items, especially regarding the construct of DCs which is too abstract and difficult to evaluate (Ali et al, 2012;Easterby-Smith et al, 2009). CDS refers to defining what is going to be measured (DeVellis, 2003).…”
mentioning
confidence: 99%